Technological features and ability to produce nisin by Lactococcus lactis subsp. lactis bv. diacetylactis obtained from dairy environment - Fusieger, Andressa (2019)
Lactococcus lactis subsp. lactis bv. diacetylactis strains are used in the dairy industry to produce acetoin and diacetyl, substances that are responsible for conferring organoleptical characteristics to some fermented foods. Bacteriocin production can be an additional beneficial feature presented by some strains. The identification and characterization of novel Lactococcus strains may reveal distinct attributes that have high technological potential for the dairy industry. This study aimed to characterize the technological and bacteriocinogenic potential of L. lactis subsp. lactis bv. diacetylactis strains obtained from dairy production systems. Twenty-three strains of L. lactis subsp. lactis isolated from cow, goat, and buffalo milks, cow's milk cream, artisanal cheeses from the Amazon region, artisanal cheeses from Marajó Island, forage peanut silages and grass silages were used in this study. The strains were identified at a biovar level (acetoin and dyacetil production, despite specific PCR assays), fingerprinted by rep-PCR and characterized for their technological potential: lactofermentation patterns, extracellular proteolytic activity, acidification capacity, and resistance to NaCl. Subsequently, the strains were subjected to PCR to detect bacteriocin-related genes (nisin, lacticins 481 and 3147, lactococcins A and 972) and further investigated by PCR and sequencing for the nisin operon. Cell free supernatants (CFS) of nisin-positive strains were tested by the spot-on-the lawn assay against a panel of 16 targets (Listeria monocytogenes - 4, L. innocua - 1, Staphylococcus aureus - 6, Lactobacillus sakei - 1, L. lactis - 4). Growth curves of 4 microbial targets (L. monocytogenes - 2, S. aureus - 2), with and without the CFS of nisin producers, were obtained by optical density (λ = 650 nm). Based on a culture collection of 23 L. lactis subsp. lactis strains, 15 presented molecular and phenotypical results that allowed them to be identified as L. lactis subsp. lactis bv. diacetylactis. The rep-PCR analysis showed 11 different genetic profiles with similarity of less than 90%, thus indicating a high level of diversity among the 15 isolates identified as L. lactis subsp. lactis bv. diacetylactis. The technological characterizations indicated that two strains did not present coagulation abilities and 13 were positive for extracellular proteolysis activity. Many of the strains were shown to efficiently acidify skim milk though two strains showed high acidifying capacities, resulting in a pH decrease over 2 units after 24h. NaCl tolerance assay revealed that all these strains were able to grow at all tested concentrations (0, 2, 4, 6, 8 and 10%); nevertheless, strains obtained from non-dairy niches presented higher tolerance to NaCl when compared to the isolated obtained from dairy niches. Eight strains presented positive results only for nisA, and only one strain (SBR4) presented the full nisin operon, confirmed by sequencing as similar to nisin Z. Only SBR4 strain presented inhibitory activity by the spot-on-the lawn assay against the 16 microbial targets. Growth curves of selected targets confirmed the inhibitory activity of the SBR4 strain, especially against S. aureus, indicating its potential for nisin production. Therefore, these results suggest that the studied strains present important technological characteristics for the food industry and that their application is viable for the production of fermented foods. In view of the technological features and the ability to produce nisin of L. lactis subsp. lactis bv. diacetylactis SBR4, it can be used to constitute a starter or mixed culture, being a strain to be considered in the dairy industry as a bioconservative and biotechnological tool.